PERKEMBANGAN EKONOMI MAKRO NEGARA MAJU DAN BERKEMBANG DI ASIA Dan EROPA: Indonesia – China, Bosnia dan Herzegovina – Jerman - A. Jalaluddin Sayuti (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2012)
As we know that the world economy is a unity, this means that a country’s economy will affect the economies other countries. Recently, an economic crisis in some European countries affecting another country’s economy through the interaction of global economic activity. Currently, the European Union is experiencing a contraction of 0,3 %, as stated in the economic recession. But on the other hand, there is an exciting area, namely Asia, where China managed to penetrate the country’s economic growth above 10% in recent years to buy securities portion in United State of America and later was asked by the European Union to increase its investment. On the other side, the real picture is that economy between countries is a unity. The 1998 crisis in Indonesia is a result from the crisis in Thailand which also extends to several South East Asia countries. This article will discuss qualitatively how the economic development of the two countries in each region – Europe and Asia. The first is in Asia; Indonesia as an example of a developing country, while China as an example of developed country. The second in the Europe region, Bosnia & Herzegovina are example of developing countries and Germany as example of developed country. The four countries will be compared its macroeconomic data of Gross Domestic Product (GDP) over the last ten years. The data used are sourced from World Bank by using the GDP applicable in billion USD, so, it will clear the economic linkage between countries